The Effectiveness of Scientific Literacy-Based Student Worksheets in Improving Student Learning Outcomes in Colloid Chemistry Learning - Rahmi, Chusnur; Maisarah, Maisarah; Sabarni, Sabarni (Journal of Educational Chemistry (JEC), 2024)
Low student learning outcomes are a significant issue in high school colloid chemistry learning. Correspondingly, this research aimed to determine the effectiveness of scientific literacy-based student worksheets (LKPD) in colloid chemistry learning. A quasi-experimental approach, specifically the pretest-posttest control group design, was employed in this study. The experimental class, XI IPA-2, consisted of 15 students, while the control class, XI IPA-1, also included 15 students, with total sampling techniques used to select the sample. Test instruments were developed to collect student learning outcome data through pretest and posttest techniques. The effectiveness of student worksheets was analyzed using the N-gain test, independent sample t-test, and effect size tests. The N-gain results exhibited an average score of 0.7319, which was a high category for the experimental class, while the control class obtained a score of 0.5308, which was categorized as moderate. The independent sample t-test results indicated a 2-taliled significance score of 0.002 (< 0.05), demonstrating a significant difference between the learning outcomes of the experimental and control classes. Based on these findings, it can be concluded that scientific literacy-based student worksheets effectively improved student learning outcomes in colloid chemistry learning at the senior high school level.